Ecosystem management in developing countries (Nairobi, Kenya, 1986)
Contents: Ecological fundamentals of environmental protection; lan-use and management; protection and use of soil.
Keywords: Agricultural ecology,Environmental management,Quản lý môi trường,Sinh thái nông nghiệp